2023
DOI: 10.3390/gels9050367
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin as an Effective Modifier of the Transport Properties of Variously Crosslinked Hydrogels

Abstract: Transport properties are one of the most crucial assets of hydrogel samples, influencing their main application potential, i.e., as drug carriers. Depending on the type of drug or the application itself, it is very important to be able to control these transport properties in an appropriate manner. This study seeks to modify these properties by adding amphiphiles, specifically lecithin. Through its self-assembly, lecithin modifies the inner structure of the hydrogel, which affects its properties, especially th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Because changes in the inner structures of hydrogel MSs may affect their ability to provide controlled drug release, the effects of reducing F(III) to Fe(II), which represented the transition from dual networks to a single network, on the releasing kinetics of ACEA were assessed. [ 40 , 41 ] Equal amounts of ACEA@CL(XGMA)‐Fe(III) MSs and ACEA@CL(XGMA)‐Fe(II) MSs were immersed in leach liquor under the protection of nitrogen. At the pre‐determined time points, a proportion of leach liquor was collected.…”
Section: Resultsmentioning
confidence: 99%
“…Because changes in the inner structures of hydrogel MSs may affect their ability to provide controlled drug release, the effects of reducing F(III) to Fe(II), which represented the transition from dual networks to a single network, on the releasing kinetics of ACEA were assessed. [ 40 , 41 ] Equal amounts of ACEA@CL(XGMA)‐Fe(III) MSs and ACEA@CL(XGMA)‐Fe(II) MSs were immersed in leach liquor under the protection of nitrogen. At the pre‐determined time points, a proportion of leach liquor was collected.…”
Section: Resultsmentioning
confidence: 99%
“…Lecithin can alter the inner hydrogel’s structure through its self-assembly and therefore its transport properties. Transport properties are one of the most crucial assets of hydrogel samples, influencing their main application potential [ 41 ]. In xerogel samples, when lecithin was added, the ability to influence transport properties was better observed as it decreased the values of the diffusion coefficient independently of the dye used and the type of crosslinking [ 41 ].…”
Section: Lecitin’s Functions In Oleogelationmentioning
confidence: 99%
“…Transport properties are one of the most crucial assets of hydrogel samples, influencing their main application potential [41]. In xerogel samples, when lecithin was added, the ability to influence transport properties was better observed as it decreased the values of the diffusion coefficient independently of the dye used and the type of crosslinking [41]. Tamura and Ichikawa (1997) reported that intermolecular 1:1 complexes were formed between lecithin and 12-HSA, which caused a structural change in the fibrous network in the 12-HSA organogel and consequently induced gel deformation [42].…”
Section: Modifier Of Hydrogel Structurementioning
confidence: 99%